Encounter between ecclesial law and Indian culture: historical background and current challenges - Pudumai Doss, Jesu (Prawo Kanoniczne, 2020)
“A culture that is steeped in wisdom, rich in human experience, and filled with spiritual values that point to God and his providence in human history”, thus St. John Paul II – in his speech to the Bishops of India on 23 June 1979 – wished “to render respectful homage to the ancient culture of your land (India)”. Speaking of the encounter between the ecclesial law and Indian culture, in the first part, a brief historical overview of Indian cultural growth is presented specifically in two areas: the four stages of Indian legal culture (Ancient Hinduism, Muslim influence, Introduction of the English system and Modern complex legislative system), and some significant moments of the presence and growth of the Church in India. In the second part, one wishes to gather the contemporary challenges, which this “encounter” has given rise to, both in the civil society (on civil recognition and some legislative implications) and in the Church (on adaptation of canon law, relationship between the sui iuris Churches, equality in the Church, inculturation and interreligious and ecumenical dialogue).